2018
DOI: 10.1186/s13063-018-2952-5
|View full text |Cite
|
Sign up to set email alerts
|

TRACE (Routine posTsuRgical Anesthesia visit to improve patient outComE): a prospective, multicenter, stepped-wedge, cluster-randomized interventional study

Abstract: BackgroundPerioperative complications occur in 30–40% of non-cardiac surgical patients and are the leading cause of early postoperative morbidity and mortality. Regular visits by trained health professionals may decrease the incidence of complications and mortality through earlier detection and adequate treatment of complications. Until now, no studies have been performed on the impact of routine postsurgical anesthesia visits on the incidence of postoperative complications and mortality.MethodsTRACE is a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This study was based on the TRACE (routine posTsuRgical Anesthesia visit to improve patient outComE) study. Details on design and analysis of the TRACE study have been previously reported [ 15 ]. TRACE was a prospective, multicenter, stepped-wedge, cluster-randomized interventional study performed between October 2016 and August 2019 in nine academic and non-academic hospitals in The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…This study was based on the TRACE (routine posTsuRgical Anesthesia visit to improve patient outComE) study. Details on design and analysis of the TRACE study have been previously reported [ 15 ]. TRACE was a prospective, multicenter, stepped-wedge, cluster-randomized interventional study performed between October 2016 and August 2019 in nine academic and non-academic hospitals in The Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…In this, all hospitals start simultaneously with a control phase providing standard care and crossing over sequentially in a randomized order to the intervention phase (routine visits). [ 3 ]…”
Section: Newer Clinical Trial Designsmentioning
confidence: 99%
“…process continues until all study sites are active, thus producing a growing "wedge" of active sites. [25][26][27] An advantage of the approach is that all trial units eventually convert to the experimental treatment (such as a specialized stroke service) that might even be nationally mandated. In contrast, the experimental treatment is only available to half the units during the trial period with a parallel-group cluster approach.…”
Section: Randomized Stepped Wedge Trialsmentioning
confidence: 99%
“…For example, the TRACE (routine posTsuRgical Anesthesia visit to improve patient outComE) trial is a prospective, multicenter, stepped-wedge, cluster-randomized trial being conducted in The Netherlands to evaluate routine postoperative visits by an anesthesiologist to reduce the risk of postoperative complications. 25 All hospitals start simultaneously with a control phase in which standard care is provided. Sequentially, in a randomized order, hospitals cross over to the intervention phase (routine visits).…”
Section: Randomized Stepped Wedge Trialsmentioning
confidence: 99%